2017
DOI: 10.3390/cancers9060060
|View full text |Cite
|
Sign up to set email alerts
|

Towards Targeting PI3K-Dependent Regulation of Gene Expression in Brain Cancer

Abstract: The PI3K pathway is one of the most highly perturbed cell signaling pathways in human cancer, including the most common malignant brain tumors, gliomas, where either activating mutations of positive pathway effectors or loss/inactivation of pathway inhibitors occurs. Knowledge of the precise transcription factors modulated by PI3K in tumor cells remains elusive but there are numerous PI3K-responsive signaling factors, including kinases, which can activate many transcription factors. In the context of cancer, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…As FGF10 activates both ERK1/2 and PI3K all the known transcription factors that depend on these kinases (e.g., ATF2, ELK1, FOS and FOXO, NFkB, CREB, respectively) ( Yang et al, 2013 ; Mantamadiotis, 2017 ) should play a role in FGF10-dependent responses. However, it is not the case for ERK1/2-regulated activation of c-FOS ( Taniguchi et al, 2003 ), suggesting that transcriptional regulation in response to FGF10/ERK1/2 signaling is complex and requires further investigation.…”
Section: Fgf10-dependent Regulators Of Intracellular Signalingmentioning
confidence: 99%
“…As FGF10 activates both ERK1/2 and PI3K all the known transcription factors that depend on these kinases (e.g., ATF2, ELK1, FOS and FOXO, NFkB, CREB, respectively) ( Yang et al, 2013 ; Mantamadiotis, 2017 ) should play a role in FGF10-dependent responses. However, it is not the case for ERK1/2-regulated activation of c-FOS ( Taniguchi et al, 2003 ), suggesting that transcriptional regulation in response to FGF10/ERK1/2 signaling is complex and requires further investigation.…”
Section: Fgf10-dependent Regulators Of Intracellular Signalingmentioning
confidence: 99%
“…Phosphatase and tensin homolog (PTEN) a tumor suppressor gene, has been reported to be involved in various types of cancer ( 15 , 16 ). Mutations in PTEN have been reported to be involved in the development of cancer ( 17 , 18 ). In various types of cancer the mutation frequency of PTEN is very high ( 19 ).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, mTORC2 is insensitive to rapamycin, which drives the glial cell proliferation, motility, and survival through the activation of AGC protein kinases [64][65][66]. However, it is found that overactivation of the PI3K/AKT/mTOR pathway reduces in the survival of glioblastoma patients and increases in the aggression of the tumor as it overstimulates processes responsible for cell proliferation, survival and migration in glioblastoma [67,68]. Therefore, researchers have identified PI3K, AKT, and mTOR as molecular targets for glioblastomas.…”
Section: Pi3k/akt/mtor Pathwaymentioning
confidence: 99%